Morbidity leading to temporary work disability - Boff, Bernadete M; Leite, Dóris F; Azambuja, Maria Inês R (Revista de Saúde Pública, 2002)
INTRODUCTION: To identify health conditions leading to benefits due to temporary work disability in a population of insured workers. METHODS: International Classification of Diseases (ICD) codes for conditions resulting in temporary work-disability (E-31) were retrieved from the National Institute of Social Security (INSS) data bank in Porto Alegre, Brazil, in 1998. The ICD codes related to the worker's disability assigned in the early medical expert examination (aX1) were used to describe the main disability causes and groups of conditions. RESULTS: A total of 6,898 disability benefits were allowed to insured workers: 1,486 (22%) were attributed to "external causes"; 1,181 (17%) to "surgery recovery" (subdivided as follows: 34% gastrointestinal; 26% genitourinary; 11% musculoskeletal; and 10% external causes ); and 4,119 (61%) to "medical conditions" (subdivided as follows: 24.8% musculoskeletal diseases; 18.9% mental diseases; and 16.2% cardiovascular diseases). When compared to a similar Brazilian study conducted in 1986, external causes moved up from fourth to the first position as a determinant of temporary work disability. CONCLUSIONS: The main causes of disability identified, accidents and violence, musculoskeletal diseases and mental diseases, are potentially associated to the worsening of the quality of life and work conditions during the study and should be a (preventive and therapeutic) priority in the nation's unified health care (SUS) agenda. The study shows the viability of referring to the INSS data bank in morbidity studies.